2004
DOI: 10.1111/j.1471-4159.2004.02402.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and function of somatostatin receptors

Abstract: This review summarizes the latest advances that have been made to elucidate the somatostatinergic system in respect to somatostatin receptor evolution, the development of receptor agonists/antagonists, receptor regulation, signal transduction, effects on cell proliferation, receptor-receptor or receptorprotein interactions and receptor function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
293
0
13

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 294 publications
(321 citation statements)
references
References 381 publications
7
293
0
13
Order By: Relevance
“…SRIF exerts its physiological effects via interaction with a family of five G-protein-coupled receptors, termed SSTR1-SSTR5 (Moller et al, 2003;Olias et al, 2004), with two splice variants of SSTR2 having been identified in mouse and rat, SSTR2A and SSTR2B (Vanetti et al, 1992, Vanetti et al, 1993. SSTRs can couple to multiple cellular effector systems, including adenylyl cyclase (AC), Ca 2+ and K + channels, phospholipase A, serine/threonine phosphatases, and tyrosine phosphatases Patel et al, 1995).…”
Section: Somatostatin and The Modulation Of Adenylyl Cyclase Activitymentioning
confidence: 99%
“…SRIF exerts its physiological effects via interaction with a family of five G-protein-coupled receptors, termed SSTR1-SSTR5 (Moller et al, 2003;Olias et al, 2004), with two splice variants of SSTR2 having been identified in mouse and rat, SSTR2A and SSTR2B (Vanetti et al, 1992, Vanetti et al, 1993. SSTRs can couple to multiple cellular effector systems, including adenylyl cyclase (AC), Ca 2+ and K + channels, phospholipase A, serine/threonine phosphatases, and tyrosine phosphatases Patel et al, 1995).…”
Section: Somatostatin and The Modulation Of Adenylyl Cyclase Activitymentioning
confidence: 99%
“…A calcium dependent mechanism known M a n u s c r i p t 10 to be important in the synthesis of NO does not seem plausible, since SRIF is known to have an inhibitory role on intracellular calcium levels (Tallent et al, 1996, Cervia et al, 2003, Olias et al, 2004. However, a mechanism involving an SH2 domaincontaining protein tyrosine phosphatase (SHP-1) may be involved, since SHP-1 was…”
Section: Retinal Physiologymentioning
confidence: 99%
“…It mediates a diverse number of physiological actions by interacting with specific receptors in the plasma membrane Thermos et al, 1989, Olias et al, 2004. Five SRIF receptor subtypes have been cloned, namely sst [1][2][3][4][5] , with the sst 2 to exist as two-splice variants sst 2A and sst 2B (Olias et al, 2004; for nomenclature see Hoyer et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations